Effect of Disulfide Bonds on the Thermal Stability of Pediocin: In-silico Screening Using Molecular Dynamics Simulation - Mehmet Altay Unal; Ozlem Kaymaz; Evrim Gunes Altuntas; Vijay K. Juneja; Ayhan Elmali (Journal of Food Protection, 2023)
The thermal stability properties of pediocin at 310, 313, 323, 333, 343, and 348 K (37, 40, 50, 60, 70, and 75°C, respectively) are reported in this study. A theoretical approach, such as the molecular dynamics method, was used to analyze the structure. Molecular dynamics simulation confirms the stability of molecules with Cys. Furthermore, this study reveals that Cys residues play an essential role in structure stability at high temperatures. To understand the structural basis for the stability of pediocin, a detailed in-silico analysis using molecular dynamics simulations to explore the thermal stability profiles of the compounds was conducted. This study shows that thermal effects fundamentally alter the functionally crucial secondary structure of pediocin. However, as previously reported, pediocin’s activity was strictly conserved due to the disulfide bond between Cys residues. These findings reveal, for the first time, the dominant factor behind the thermodynamic stability of pediocin.